Women who stay behind : pedagogies of survival in rural transmigrant Mexico - Trinidad Galván, Ruth (The University of Arizona Press, 2015)
"The book uncovers the social, educational, and cultural tools rural Mexican women employ to creatively survive the conditions created by migration. It addresses the material conditions that lead to the migration of adults from the area, but at the core are the educational and personal endeavors of women to get ahead without the men in their families"--Provided by publisher